2023
DOI: 10.2147/ijgm.s400420
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Aspiration Pneumonia Among Stroke Patients in Western Amhara Region, North-West Ethiopia: A Retrospective Follow Up Study

Abstract: Background Aspiration pneumonia is one of the major complications among hospitalized stroke patients, with global incidence ranging from 5–83% and hospital mortality rate of up to 70%. This study aimed to assess the incidence and identify predictors of aspiration pneumonia among stroke patients in Western Amhara region, North-West Ethiopia. Methods An institution-based retrospective follow-up study was conducted on a simple random sample of 568 stroke patients in Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The control group exhibited the highest proportion of AP cases (21.1%), while the ACEi + BB group had the lowest proportion (12.1%). These findings suggest that the control group, representing individuals receiving neither ACEi nor BB therapy, may be more predisposed to develop AP, as supported by related studies [ 37 , 38 ]. Further, patients diagnosed with AP rather than non-AP were found to have significantly higher PSI and CURB-65 scores across all four treatment groups, emphasising greater disease severity with AP compared to non-AP, irrespective of the treatment regimen.…”
Section: Discussionsupporting
confidence: 75%
“…The control group exhibited the highest proportion of AP cases (21.1%), while the ACEi + BB group had the lowest proportion (12.1%). These findings suggest that the control group, representing individuals receiving neither ACEi nor BB therapy, may be more predisposed to develop AP, as supported by related studies [ 37 , 38 ]. Further, patients diagnosed with AP rather than non-AP were found to have significantly higher PSI and CURB-65 scores across all four treatment groups, emphasising greater disease severity with AP compared to non-AP, irrespective of the treatment regimen.…”
Section: Discussionsupporting
confidence: 75%
“…According to the data obtained, inhibition of cholinergic signaling by vagotomy or the use of mice with nicotinic acetylcholine receptor deficiency stimulated an increased immune response and prevented pneumonia after stroke. These results showed an association between the cholinergic pathway and the risk of developing pneumonia (15). Due to reduced chewing, salivation, swallowing and oral hygiene, patients with acute stroke are particularly vulnerable to disruption of the microbial ecology of the oral cavity.…”
Section: Pathogenesis and Risk Factors Of Sapmentioning
confidence: 90%
“… 52 , 53 Aspiration pneumonia is one of the most important complications among hospitalized stroke patients. 54 Lidetu et al 55 found that the risk of developing aspiration pneumonia in patients with vomiting and dysphagia was higher than in patients without vomiting and dysphagia. For these reasons, it is considered natural for caregivers to associate nausea and vomiting with aspiration.…”
Section: Discussionmentioning
confidence: 99%